Pengembangan Sistem ERP Berbasis Web Menggunakan Next.js dan Laravel: Pendekatan Prototyping SDLC - Andreas Natanael Irawan; Amadea Permana Sanusi (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
The development of information technology encourages companies to digitize business processes to improve the efficiency and accuracy of data management. CV AS Nusa Trans (CV ANT), a land transportation service company, still uses manual spreadsheet-based recording scattered across multiple links, causing problems such as data duplication, information delays, and difficulties in preparing reports. This research aims to develop a web-based Enterprise Resource Planning (ERP) system as an integrated digital solution to support company operations. The development was carried out using the System Development Life Cycle (SDLC) Prototyping model approach, which allows user involvement from the early stages through an iterative process. Next.js is used as a front-end framework to produce a responsive and fast interface display, while Laravel is used as a back-end to ensure a secure and organized business logic structure. The system design process includes observation, requirements analysis, system modeling and iterative prototype implementation. The developed ERP system integrates invoice management, fleet management, customer data, and an operational calendar into a single centralized platform. To evaluate system usability, the System Usability Scale (SUS) method was applied involving two main user roles: Admin and Owner. The evaluation results indicate an average SUS score of 93.75, which falls into the Excellent Usability category, demonstrating that the system is easy to learn, efficient to use, and well accepted by users. This research contributes scientifically by demonstrating the effectiveness of combining the SDLC Prototyping approach with modern Web Application technologies (Next.js and Laravel) in the development of an ERP system, particularly within the land transportation service sector.